Factors associated with pregnancy desire among adolescent women in five Latin American countries: a multilevel analysis. (7th July 2018) - Estrada, F; Suárez‐López, L; Hubert, C; Allen‐Leigh, B; Campero, L; Cruz‐Jimenez, L
Abstract : Objective: To explore demographic, socio‐economic, and reproductive factors associated with pregnancy desire among adolescents in five Latin American countries. Design: Secondary analysis using nationally representative, cross‐sectional data from UNICEF Multiple Indicator Cluster Surveys (MICS). Setting: Cuba, the Dominican Republic, El Salvador, Mexico, and Panama. Population: Adolescents 15–19 years old who were pregnant or mothers ( n = 4207). Methods: Chi‐square tests, simple linear regressions, and multilevel Poisson regression models were used to estimate associations between individual‐ and country‐level factors associated with pregnancy desire among adolescents. Main outcome measures: Desire for pregnancy among adolescents who were pregnant or had given birth in the last 2 years. Results: The proportion of adolescents who reported they desired their last pregnancy ranged from 79.3% in Cuba to 37.6% in Panama; approximately half the adolescents in Mexico, El Salvador, and the Dominican Republic desired their last pregnancy. The multilevel analysis shows that pregnancy desire was more likely among adolescent women who were less educated [prevalence ratio (PR) = 0.97, 95% confidence interval (CI) 0.96–0.98], older (PR = 1.39, 95% CI 1.04–1.09), married or cohabiting with a partner (PR = 0.70, 95% CI 0.53–0.93), and had low parity (PR = 0.67, 95% CI 0.58–0.76). Conclusions: Adolescents with less education, who are older, married or cohabiting, and with low parity were more likely to desire their pregnancy. These data constitute evidence that, in conjunction with qualitative and implementation research, can be used to better design services for adolescents so they can exercise their sexual and reproductive rights, and plan healthier and more satisfying futures. Funding: All the databases used on the performance of this study are open access. We did not receive any funding for the present analysis. Tweetable abstract: Parity and marital status showed the strongest association with adolescent pregnancy desire in five Latin American countries. Abstract : Tweetable abstract Parity and marital status showed the strongest association with adolescent pregnancy desire in five Latin American countries.